Konseptualisasi News Vodcast: Jurnalisme Baru untuk Khalayak Muda - Wiguna, Okta; Famega Syavira Putri; Nur Aziza Sasmi , Nanda Adjeng Castity (Jurnal Pewarta Indonesia, 2025)
Podcasts incorporating video elements are emerging as a strategic content innovation among traditional media outlets, particularly as a means to engage younger audiences. The effectiveness of this format is exemplified by the success of the award-winning Bocor Alus Politik podcast, produced by Tempo. However, this trend presents a new challenge for academic inquiry, as existing conceptualizations of podcasts primarily assume an audio-based format, overlooking the production and consumption dynamics introduced by visual elements. This paper seeks to establish a new conceptual definition of the "news vodcast"—a news podcast incorporating video—by employing a conceptual paper methodology with a theory synthesis approach and a systematic literature review for data collection. Drawing on 52 scholarly sources from media studies and education, this study proposes that a news vodcast constitutes an audiovisual journalism product characterized by an informal and narrative journalism style, produced periodically and distributed as video-on-demand content via the internet and streaming platforms. This conceptual framework serves as the foundation for a research agenda that positions news vodcasts as a distinct journalistic format, separate from traditional audio-only podcasts.